REGARDING THE CLASSIFICATION OF PHRASEOLOGICAL UNITS IN ENGLISH - Khatamova Ziyoda Ghulomovna (Galaxy International Interdisciplinary Research Journal, 2022)
It is known that in English and American linguistics, the term "phraseological unit" is not a term (phraseological unit), but a word called "stable expression" that essentially means the same thing, and along with the latter, Idiom (idioma) concept is also used. In English linguistics, idiom does not mean the narrow meaning of a phraseological combination, but all fixed phrases in general.